The vicar of Dibley. [videorecording (DVD)] Series 2 - French, Dawn; Waldhorn, Gary, 1943-; Fleet, James (BBC Video ; Distributed by Warner Home Video, 2003)
The sleepy English village of Dibley is plunged into an uproar when its new vicar turns out to be a woman. And not just any woman, but the unconventional Geraldine Granger who brings her own earthy spirit and humor to the pulpit.